Development of an analytical model for optimisation of the ultrasonic consolidation of composite prepreg. (15th April 2022) - Flora, Francesco; Rizzo, Francesco; Pinto, Fulvio; Meo, Michele
Abstract: Mechanical properties of composite laminates are directly affected by the level of porosity of the part. Therefore, it is important to ensure that an adequate air debulking is provided during the manufacturing in order to obtain high quality products. The use of ultrasonic waves during the hand lay-up of prepreg layers can enhance this step. In a previous work we have demonstrated that this technique, named ultrasonic consolidation (UC), can lead to a large reduction in terms of manufacturing time and improvements of the Interlaminar Shear Strength (ILSS) of the final part. In this work, a model is proposed to analytically describe the influence of the ultrasonic stimulation on the air flux through the material and optimise the procedure, showing how the use of ultrasonic waves significantly increases the net air flow rate, particularly for small radius voids. The study provided some guidelines for the optimisation of the process parameters such as the frequency and location of the transducers. The efficiency of the method was experimentally validated by manufacturing several samples using UC debulking procedure with three exposition times (5-10-15 min). Microscope images showed a large decrement (up to 96%) of the voids projected area in samples section in comparison with reference. Flexural and Charpy impact properties were evaluated through mechanical tests, showing properties comparable to the reference samples, with improvements in terms of flexural modulus (up to 9%). Results from the analytical study and experimental tests indicate that the UC process is a reliable debulking procedure for the hand lay-up of prepreg that largely reduces manufacturing time and voids content, leading to improvements of the mechanical properties of the final part.